Comparison of high voltage circuit breakers performances at Jabatan Senggaraan Aset (Kedah & Perlis), TNB Transmission Division / Mohammad Zulfahmi Khairul Anwar - Khairul Anwar, Mohammad Zulfahmi (2012)
This paper describes the comparison of high voltage circuit breakers performances at Jabatan Senggaraan Aset (Kedah & Perlis). The comparisons are between the operating mechanisms and model of circuit breakers by using a routine maintenance test. At the end of this paper, one type of the operating mechanism and model of circuit breaker will be suggested to be the best performance of CB in JSA (Kedah & Perlis).